MAKNA ESTETIKA YANG TERKANDUNG PADA PUISI "PAHLAWAN YANG SOK PAHLAWAN" KARYA REMY SYLADO - Pamungkas, Tegar Ihsan Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The research on the poem "Heroes Who Become Heroes" is motivated by the existence of poetry that is rarely heard by some people. The research on the pretended hero poem is motivated by the existence of the pretended hero poem drowning at this time, especially the Indonesian people who look down on, do not order, and not aesthetic. The research method used is a qualitative method using descriptive techniques that describe the condition of the subject and object of research based on existing data. The birth of the heroic heroic poem was originally driven by an imbalance in the meaning of the words hero and heroic in everyday life. After the writer looks for references and gets the date about the poetry to be studied, the writer will present it in this article. Remy Sylado not only broke the feudal attitude and the New Order regime, but also legalized or formalized literary aesthetic view of mbeling poetry.